Assembling the challenging puzzle of algal biodiversity: species delimitation within the genus Asterochloris (Trebouxiophyceae, Chlorophyta) - Škaloud, Pavel; Steinová, Jana; Řídká, Tereza; Vančurová, Lucie; Peksa, Ondřej (Journal of phycology, 2015)
The genus Asterochloris represents one of the most common, widespread, and diverse taxa of lichen photobionts. In this report, we describe and characterize six new species (A. echinata, A. friedlii, A. gaertneri, A. leprarii, A. lobophora, and A. woessiae) that were identified during our recent investigation of photobiont diversity. We found that the species differed genetically, morphologically, ecologically, and with respect to their mycobiont partners. Statistical analyses revealed significant morphological differentiation of all six newly described species, as well as their separation from previously described Asterochloris species. Chloroplast morphology represented the best morphological marker for species delineation. In fact, each species can be recognized by the dominance and unique assemblage of particular chloroplast types. Although genetically well recognized by rapidly evolving internal transcribed spacer rDNA and actin intron markers, all 13 investigated Asterochloris species shared identical small subunit rDNA sequences. We therefore demonstrated that morphologically and ecologically diverse species can frequently be grouped into a single taxonomic unit in whole-transcriptome sequencing studies, considerably affecting the resulting estimates of species diversity. Finally, we demonstrated the presence of isogamous sexual reproduction in Asterochloris, disputing the current symbiotic dogma of the loss of sexual reproduction in algal symbionts.
Keywords: speciation; phylogeny; symbiosis; green algae; morphology; taxonomy; lichens; Asterochloris; cryptic species